MORPHOMETRIC CHARACTERISTICS OF RAT SALIVARY GLANDS HEMOMICROVASCULATURE CAPACITY COMPONENT UNDER NORMAL CONDITIONS AND IN ETHANOL CHRONIC INTOXICATION - Yeroshenko, G.A.; Shevchenko, K.V.; Yakushko, O.S. (World of Medicine and Biology, 2018)
Data of the morphometric study on chronic ethanol intoxication are presented in the paper. It has been established that chronic ethanol intoxication affects the capacitive link of the hemomicrovasculature of the submandibular salivary glands. At the early stages of observation, venules dilation is determined, which is confirmed by a significant increase in the outer diameter and the lumen diameter with the vascular wall thickness reduction. From the twelfth day the tendency is observed towards the metric indices restoration. Normalization of the indices is not determined by the thirtieth day.